AN EXAMINATION OF THE STRUCTURE AND DETERMINANTS OF BRANDS LOYALTY ACROSS HOTEL BRAND ORIGIN - SUHARTANTO, DWI (ITB Journal Publisher, LPPM ITB, 2011)
This study reports an assessment of brand loyalty across the origin of the brand in the hotel industry. This study endeavours to extend recent advances in services marketing theory on brand loyalty to the international and domestic brand level of analysis. Brand loyalty is proposed to consist of three dimensions (attitudinal loyalty, conative loyalty and behavioural loyalty) with service quality, perceived value, customer satisfaction, and brand image as its determinants. The results, drawn from sample of four-star hotels, support the proposed brand loyalty model across international and domestic hotels. Service quality, perceived value, and customer satisfaction are important antecedents of brand loyalty though brand image has a strengthening role in these three loyalty determinants in both international and domestic hotels. Overall, the effects of these determinants on brand loyalty differ between international and domestic hotels.